Low-Skill Products by High-Skill Workers: The Distributive Effects of Trade in Emerging and Developing Countries - Menéndez González, Irene; Owen, Erica; Walter, Stefanie (Comparative political studies, 2023)
In developing countries, trade is increasingly associated with greater returns to high-skilled labor and rising inequality. These empirical patterns are at odds with canonical models of trade in the developing world. What does this mean for the political economy of trade in these countries? We argue that although developing countries have a comparative advantage in low-skill products, these are produced by workers that are relatively high-skilled compared to their peers. Trade and global production benefit relatively skilled workers, particularly those exposed to exports and inward foreign direct investment in manufacturing. Our argument offers insight into why relatively skilled workers are most supportive of free trade and why inequality is rising in developing countries. We examine micro- and macro-level implications of our argument using cross-national survey data on policy preferences and aggregate data on trade and inequality. The findings have important implications for the political economy of trade and global production in developing countries.